Written Preparation for History Class - Marsenić, Miloš (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Teaching is an organized and planned work process that accomplishes the tasks of upbringing and education. The success of teaching depends on the quality of planning. The lecturer has the obligation to perform planning continuously. Planning can be annual, monthly, and daily, and for the processing of each teaching unit, it is necessary to have the class prepared. Class is the basic time unit for planning educational work in the school. Each lesson must be preceded by the appropriate written preparation of the teacher. It should not be an obligation but a need for the material to be successfully mastered. Every class is special and with good preparation mistakes and shortcomings are minimized. Each writing preparation for a class has several phases: professional, didactic-methodical, and technical preparation. After these phases, the making of written preparation is approached. It should contain the following elements: name of the school, name of the teacher, name of the subject, grade and class, date, the ordinal number of class, teaching topic, teaching unit, type of class, goals and tasks of the class, form of work, teaching methods, teaching aids, correlation with other subjects, class flow, homework, the layout of the board and observations about the class. The methodology of teaching history has similarities with the methods of other subjects, but also its peculiarities, due to its subject of work, history.